Asymmetric flow and mass transfer of twin-liquid films. (15th September 2022) - Xie, Hanguang; Shen, Lian; Dai, Gance
Highlights: An improved VOF-based subgrid-scale model for mass transfer simulation. Complicated time-periodic flow behavior of asymmetric twin-liquid films. Several interesting concentration patterns produced by vortices. Global mass transfer enhancement by large waves and vortices. Abstract: Twin-liquid films are a combination of wall-bounded films and confined free films. The asymmetric flow is investigated with the VOF method. A new integration algorithm is developed for interfacial mass transfer ( Pe =8400) with the subgrid-scale model [1] . Due to the dynamic balance of the surface tension and the spanwise inertia force, periodic interface oscillation at the lower edge of the window is observed. Then the capillary waves in the window become asymmetric, which induces different flux distributions on two sides of the lower wall, accompanied by large waves and vortices. The vortices extrude a scalar plume (local high concentration liquid) from the interface into the liquid bulk and roll it up once or twice in a reverse direction, significantly promoting the mixing and diffusion of scalar in the liquid bulk. As a result, the local mass transfer rate can be enhanced by 100%∼400% on the lower wall.